Grip-load force coordination in cerebellar patients - Serrien, D.J.; Wiesendanger, Mario (Experimental brain research, 1999)
The study examined the anticipatory grip force modulations to load force changes during a drawer-opening task. An impact force was induced by a mechanical stop which abruptly arrested movement of the pulling hand. In performing this task, normal subjects generated a typical grip force profile characterized by an initial force impulse related to drawer movement onset, followed by a ramp-like grip force increase prior to the impending load perturbation. Finally, a reactive response was triggered by the impact. In patients with bilateral cerebellar dysfunction, the drawer-opening task was performed with an alternative control strategy. During pulling, grip force was increased to a high (overestimated) default level. The latter suggests that cerebellar patients were unable to adjust and to scale precisely the grip force according to the load force. In addition, the latency between impact and reactive activity was prolonged in the patients, suggesting an impaired cerebellar transmission of the long-latency responses. In conclusion, these data demonstrate the involvement of cerebellar circuits in both proactive and reactive mechanisms in view of predictable load perturbations during manipulative behavior.